(untitled) (The Research of Medical Science Review, 2025)
Background: Effective teamwork in Medical Emergency Teams (METs) is essential for delivering safe and efficient patient care. Inadequate communication and coordination among healthcare professionals, especially in emergency settings, often lead to compromised patient safety. Objective: This study aimed to identify the teamwork-related needs of METs from the perspective of registered nurses, with a focus on communication, leadership, role clarity, and collaboration. Materials and Methods: A quantitative cross-sectional study was conducted among 86 registered ICU nurses at the Punjab Institute of Neurosciences, Lahore. Participants were selected using purposive sampling. Data were collected using a structured questionnaire based on the Team Assessment Questionnaire (TAQ) and analyzed through SPSS v23 using descriptive statistics and ANOVA. Results: The findings revealed high agreement among nurses on positive aspects of team identity, leadership, communication, and performance. However, areas such as constructive feedback and conflict resolution showed room for improvement. ANOVA results indicated no significant association between years of experience and perception of teamwork (p = 0.385). Conclusion: Nurses perceive teamwork in METs positively but highlight the need for enhanced feedback mechanisms and conflict management. Targeted training programs and leadership development are recommended to strengthen collaboration and improve patient outcomes.